John William Dawson : faith, hope, and science - Sheets-Pyenson, Susan, 1949- (McGill-Queen's University Press, 1996)
Drawing on Dawson's correspondence and personal papers, Susan Sheets-Pyenson paints an intimate portrait of a pivotal figure in Canada's scientific heritage and a proper Victorian gentleman whose pious Presbyterianism, missionary zeal, and unwavering belief in the light of knowledge drove him on a quest to conquer ignorance, prejudice, and bigotry.